Hyperfine-interaction-driven Aharonov-Bohm effect in mesoscopic rings - Vagner, I.D.; Wyder, P.; Rozhavsky, A.S. (Физика низких температур, 1997)
It is shown qualitatively that lifting of the electron spin degeneracy by a hyperfine field, which is generated by a nonequilibrium nuclear spin distribution, and breaking of the left-right symmetry by the spin-orbit interaction in a closed ring produces under certain conditions a persistent current, which demonstrates the Aharonov-Bohm-like oscillations with time in GaAs / AlGaAs-based mesoscopic rings even m the absence of an external magnetic field. The typical time interval of these (mesonucleospinic) oscillations is of the order of several seconds, which is typical of the nuclear spin relaxation times in heterojunctions.